2021
DOI: 10.1103/physrevb.104.l180304
|View full text |Cite
|
Sign up to set email alerts
|

Quantum repetition codes as building blocks of large-period discrete time crystals

Abstract: Discrete time crystals (DTCs) are exotic many-body phases of matter in which some observables exhibit robust subharmonic response to periodic driving. By highlighting the connection between DTCs and a quantum error correction model, we devise a general and realistic scheme for building DTCs exhibiting large period observable dynamics. This is accomplished by utilizing a series of Ising spin-1/2 chains, each of which simulates a quantum repetition code at the hardware level, and devising a time-periodic Hamilto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…It has been shown that coupling TCs to entangled systems prevents the otherwise very fragile quantum entanglement from rapid decay due to the interactions of these entangled systems with the external environment [13]. Therefore, it has been proposed that TCs are very appropriate candidates to be applied for the development of memory-storing apparatus for quantum computers [16]. In addition, recently it has been discussed that a set of TCs can be used as a model to simulate the human brain [17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that coupling TCs to entangled systems prevents the otherwise very fragile quantum entanglement from rapid decay due to the interactions of these entangled systems with the external environment [13]. Therefore, it has been proposed that TCs are very appropriate candidates to be applied for the development of memory-storing apparatus for quantum computers [16]. In addition, recently it has been discussed that a set of TCs can be used as a model to simulate the human brain [17].…”
Section: Introductionmentioning
confidence: 99%